Kualitas Pelayanan sebagai Jembatan antara Akreditasi dan Kepercayaan Publik Rumah Sakit - Widodo, Asep Tri; Haninun, Haninun (Jurnal EMT KITA, 2026)
This study aims to analyze the effect of accreditation of the Zaenal Abidin Pagar Alam Regional General Hospital (RSUD) in Way Kanan Regency on public image and trust, with service quality as a mediating variable. The background of this study is based on the phenomenon of a decrease in the number of outpatients and inpatients over the past six months even though the hospital has obtained Plenary accreditation. This study uses a quantitative approach with a causal research type. A sample of 100 respondents was obtained through accidental sampling technique. Data collection was carried out using a questionnaire, while data analysis used SmartPLS 3 through validity and reliability testing, as well as path analysis to determine direct and indirect effects.